Bioindicadores de qualidade do solo em um sistema integrado de produção agropecuária - Neufeld, Ângela Denise Hübert (2016)
Integrated crop‑livestock systems (ICLS) can improve the chemical, physical and biological soil attributes. However, grazing intensification may outweigh these benefits and cause severe losses to the system. Soil biota is considered a good environmental bioindicator and can attest to the quality of the system management. This study aimed to know the implications of grazing intensification on soil biota in a long-term ICLS, to verify which soil conditions most influence biological attributes, and to evaluate if these attributes can be used as environmental quality indicators in ICLS. The experiment was started in 2001, on a 23 hectare area, with Glycine max in summer and Avena strigosa+Lolium multiflorum for continuous cattle grazing in winter. The treatments consisted of four sward heights (10, 20, 30, and 40 cm), plus an ungrazed area, as the control. Sampling was performed in four seasons between 2014-2016, two after the grazing season and two after soybean harvest. Soil basal respiration, microbial biomass carbon (MBC), microbial quotient, diversity and abundance of meso and macrofauna, as well as chemical, physical and vegetation cover variables were evaluated for correlation. The highest microbial respiration, MBC content, abundance and diversity of the soil fauna were quantified under moderate (20 and 30 cm) and light (40 cm) grazing intensities and under no grazing. At the high grazing intensity was a vegetal cover reduction and decreasing on the physical soil quality, which resulted in a lower soil moisture and activity, abundance and diversity reduction of soil organisms community. These results increase the need for an adequate management of pasture areas, without harming the ICLS sustainability.